IMPLIKASI PERTANAHAN DALAM PENANGANAN KONFLIK AGRARIA DI INDONESIA - Aksnudin, Saim - (LITIGASI, 2023)
This research analyzes the implications of land issues in handling agrarian conflicts in Indonesia using a normative juridical analysis method. By examining legislation, court decisions, and legal experts' opinions, this study reveals the close relationship between land issues and agrarian conflicts in Indonesia. The analyzed implications of land include regulatory aspects, legal certainty, and understanding of land issues in resolving agrarian conflicts. The research findings indicate that unclear, overlapping, or conflicting legislation can hinder the resolution of agrarian conflicts. Moreover, the divergence of court decisions significantly impacts the handling of agrarian conflicts. Legal experts' opinions also provide diverse perspectives on the implications of land in the context of resolving agrarian conflicts. To achieve sustainable resolution of agrarian conflicts, effective coordination among relevant institutions is necessary to improve land regulations, ensure legal certainty, and enhance understanding of land issues. Additionally, efforts to promote dialogue and community participation need to be strengthened in handling agrarian conflicts. Keywords: Land, Agrarian Conflict, Implications, Legal Certainty, Conflict Resolution.